Caspase-dependent inactivation of proteasome function during programmed cell death in Drosophila and man - MARTIN, SEAMUS JOSEPH; CREAGH, EMMA (The American Society for Biochemistry and Molecular Biology, 2004)
The caspase family of cysteine proteases plays a conserved role in the coordinate demolition of cellular structures during programmed cell death from nematodes to man. Because cells undergoing programmed cell death in nematodes, flies, and mammals all share common features, this suggests that caspases target a common set of cellular structures in each of these organisms. However, although many substrates for mammalian caspases have been identified, few substrates for these proteases have been identified in invertebrates. To search for similarities between the repertoires of proteins targeted for proteolysis by caspases in flies and mammals, we have performed proteomics-based screens in Drosophila and human cell lines undergoing apoptosis. Here we show that several subunits of the proteasome undergo caspase-dependent proteolysis in both organisms and that this results in diminished activity of this multicatalytic protease complex. These data suggest that caspase-dependent proteolysis decreases protein turnover by the proteasome and that this is a conserved event in programmed cell death from Drosophila to mammals.
PUBLISHED
Keywords: Immunology; cell death